Causes of the economic crisis in Southeast Asia - Živilė Bieliūnaitė (Politologija)
The essay examines internal (institutional) as well as external causes of the economic crisis in Southeast Asia (South Korea, Indonesia, Malaysia, Thailand, and the Philippines) in 1997–98. It is argued in the essay that the crisis in the above-mentioned countries resulted from the coincidence of their weak/weakened institutional structures and negative external impacts, i.e., incapacity of national governments to control global capital flows, "contagion" originating from countries' economic interdependence, and improper behavior of external actors, such as the IMF.